Automation of ride orders for passenger vehicles - Terzić, Rajko M.; Eremija, Zoran S.; Terzić, Dušan R. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Effective functioning of organizations depends on the quality of management of interconnected and interdependent business processes.The key problem in the projects implementation is associated with ignorance of business processes of a business itself.The paper provides an approach for modeling business processes through a selection of tried and tested methods and models for coping with the complexity of systems.Business high-level features are decomposed into smaller functional units, resulting in a hierarchical structure of business functions of different granularity. At the bottom of the functional decomposition hierarchy,there are so-called primitive functions which are in fact managing processes.The specifications of the interactions between the systems participants are use case diagrams.The specification of business processes has been realized through BPMN diagrams (choreographies and collaboration diagrams).An automated solution improves the quality of operations and coordinates all participants in this business system. In this paper,the business analysis method has been presented as well as the results of the design of the segment called “aride order for passenger vehicles” and the business processes closely associated with it.